Socio-psychological factors of the activity of territorial communities in the conditions of decentralization - Tulin, Kyrylo (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article analyzes democratic decentralization, which provides for the formation of local self-government councils of the appropriate level, which represent the interests of the inhabitants of a certain territory, and there are no subordination relations between the councils of different levels. It is analyzed that the first step of modern reforms in Ukraine was administrative-territorial reform and, accordingly, creation of united territorial communities. It is analyzed that among the main obstacles to the implementation of effective decentralization reform are low activity of citizens, their unwillingness to take responsibility and make decisions. It is the low activity of the communities that makes it possible to manage the decentralization process from above, by the regional leadership. The article is a study of socio-psychological factors of the activity of territorial communities in the conditions of decentralization. A number of problems were found which stimulated the increase of activity of territorial communities. The dynamics of increase in the number of OTs in 2015–2018 in all regions of Ukraine is analyzed. It is considered that financial decentralization has also become one of the main factors in increasing population activity. It is noted that a considerable part of the population of territorial communities are ready to participate in public events. Analyzed that the key advantage of the new status of communities in the context of decentralization is the significant increase in the financial resources they can dispose of. It is determined that the union of territorial communities in terms of administrative-territorial reform and decentralization of power has opened wide opportunities for the development of institutes of self- organization of the population and local self-government, change of the model of organized "from above" society, which is a mechanism of restraining the creative potential of the nation and blocking the self-realization of human life, to an organized "bottom" that eliminates the contradiction between the citizen and the state.
Keywords: activity; territorial community; decentralization; financial decentralization; self-organization of the population; public events